Factors influencing corporate social responsibility disclosures in Nepalese banks - Gopi Bidari; Hadrian Geri Djajadikerta (Emerald Publishing Limited, 2020)
This paper examines the relationship between selected firm-specific variables and the extent of corporate social responsibility (CSR) disclosures made by Nepalese banks.A content analysis approach of the banks' annual reports is applied using a CSR disclosure index based on the Global Reporting Initiative guidelines. The factors identified in this study – bank size, bank age and bank profitability – are analyzed against the extent of CSR disclosures in the Nepalese banks using multiple regression.The main finding from the content analysis indicates that the extent of CSR disclosures made by Nepalese banks in their annual reports is mostly descriptive, with charity and donation being the most disclosed items. The main findings from the correlation and regression analyses show that there are positive and significant relationships between both bank size and profitability and the extent of CSR disclosures in the Nepalese banks, while bank age is a partial determinant.Banks have a significant role in the Nepalese economy. This study offers insights into the CSR disclosure practices of Nepalese banks, examines the potential factors affecting CSR disclosure and expands the pool of CSR knowledge in the developing country context, especially in the banking sector.